(untitled) (Baghdad Science Journal, 2020)
The ability of beans (Phaseolus vulgaris L.) to uptake three pharmaceuticals (diclofenac, mefenamic acid and metronidazole) from two types of soil (clay and sandy soil) was investigated in this study to explore the human exposure to these pharmaceuticals via the consumption of beans. A pot experiment was conducted with beans plants which were grown in two types of soil for six weeks under controlled conditions. During the experiment period, the soil pore water was collected weekly and the concentrations of the test compounds in soil pore water as well as in plant organs (roots, stems and leaves) were weekly determined. The results showed that the studied pharmaceuticals were detected in all plant tissues; their concentrations in plant roots were higher than plant stems and leaves. The extent level and accumulation of the studied pharmaceuticals in sandy soil was higher than the clay soil. The concentration of diclofenac in plant tissues was higher than both of mefenamic acid and metronidazole, indicating that diclofenac is more available to plant. The content of dissolved pharmaceuticals in soil pore water decreased gradually over time during the experimental period confirming the ability of beans to uptake these pharmaceuticals from soil. The results suggest the possibility of studying pharmaceuticals to be accumulated in beans tissues despite their low concentrations in the studied soils. Our results showed that the studied pharmaceuticals were detected in all plant tissues; their concentrations in plant roots were higher than plant stems and leaves. The extent level and accumulation of the studied pharmaceuticals in sand soil was higher than the clay soil. The concentration of diclofenac in plant tissues was higher than mefenamic acid and metronidazole, indicates that diclofenac is more available to plant. The content of dissolved pharmaceuticals in soil pore water decreased gradually over time during the experimental period which confirming the susceptibility of beans to uptake these pharmaceuticals from soil. Our results suggest the possibility of studied pharmaceuticals to be accumulated in beans tissues despite their low concentrations in the studied soils.